Kognisi Sosial Dalam Narasi Terstruktur, Sistematis, dan Masif (TSM) di Persidangan Pemilu Pilpres 2019 Melalui Uji Linguistik Forensik - Romdlon, Atiq Mohammad; Fidiyanti, Murni; Syaikhu, Ahmad; Rosyidi, Zudan (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2022)
This study analyzes social cognition on TSM (structured, systematic, and massive) narrative created by the lawyers of the presidential election pair (paslon) 2 during the 2019 presidential election dispute hearing at the Constitutional Court (MK). The representation of social cognition is in the form of knowledge which includes the principles of